2008
DOI: 10.1590/s1413-70542008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de duas cultivares de chicória em três ambientes de cultivo

Abstract: RESUMOPelo crescente aumento da importância econômica e perante a escassez de informações técnicas para o cultivo da chicória (Cichorium endivia L.), objetivou-se com o presente trabalho avaliar o comportamento de duas cultivares em três ambientes de cultivo, no período de 11/09/04 a 04/12/04, em Ponta Grossa (PR). Os tratamentos foram arranjados em parcela subdividida, constituindo-se a parcela em ambientes de cultivo (túnel baixo, agrotêxtil branco e ambiente natural) e a subparcela em cultivares (AF-254 e M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…Cardoso & Ustulim Filho (2013), using the same cultivar, obtained an average height of 18.4 cm and the highest fresh matter of 389 g. For fresh matter, Reghin et al (2007) obtained 332-407 g, very similar results obtained in this study (372 g of fresh matter in the best treatments). The values are also similar to those obtained by Feltrim et al (2006) and Sá & Reghin (2008).…”
Section: Comparison Of Doses Of Organic Compost With Inorganic Fertilsupporting
confidence: 92%
“…Cardoso & Ustulim Filho (2013), using the same cultivar, obtained an average height of 18.4 cm and the highest fresh matter of 389 g. For fresh matter, Reghin et al (2007) obtained 332-407 g, very similar results obtained in this study (372 g of fresh matter in the best treatments). The values are also similar to those obtained by Feltrim et al (2006) and Sá & Reghin (2008).…”
Section: Comparison Of Doses Of Organic Compost With Inorganic Fertilsupporting
confidence: 92%
“…This may be due to the low temperatures during P2 and P3 (Table 1). According to Sá & Reghin (2008), minimum temperatures of 8 and 9°C may slow escarole development, consequently, as observed in this study, it was necessary to increase the number of days to reach the harvest point that is not desired for leafy vegetables. In this context, Feltrim et al (2006) reported that lower amplitudes may provide better escarole development, justifying results observed for growing periods.…”
Section: Resultsmentioning
confidence: 81%
“…Temperatures below 8°C soon after transplanting increase escarole cycle, however, temperatures above 40°C negatively affect to crop (SÁ; REGHIN, 2008), because acceleration in metabolism results in less accumulation by plants. From this aspect, it can be inferred that the average temperatures observed at these seasons may have been adequate to provide plants with greater photosynthetic area, and consequently greater photoassimilated production and translocation, resulting in greater growth and development , ending the cycle more quickly.…”
Section: Resultsmentioning
confidence: 99%